/
/
/
Find the average rate of change for the function over the given interval. 1) y = x2 + 3x between x = 2 and x = 5
Not my Question
Flag Content

# Question : Find the average rate of change for the function over the given interval. 1) y = x2 + 3x between x = 2 and x = 5 : 2151560

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Find the average rate of change for the function over the given interval.

1) y = x2 + 3x between x = 2 and x = 5

A) (40/3)

B) 6

C) 10

D) 8

2) y = 2x3 + 8x2 + 7 between x = -2 and x = 8

A) 152

B) 190

C) (1543/10)

D) (1543/8)

3) y = √(2x) between x = 2 and x = 8

A) - (3/10)

B) 7

C) 2

D) (1/3)

4) y = (3/x - 2) between x = 4 and x = 7

A) 7

B) (1/3)

C) 2

D) - (3/10)

5) y = 4x2 between x = 0 to x = (7/4)

A) 2

B) (1/3)

C) - (3/10)

D) 7

6) y = -3x2 - x between x = 5 and x = 6

A) (1/2)

B) -2

C) -34

D) - (1/6)

7) y = x3 + x2 - 8x - 7 between x = 0 and x = 2

A) -2

B) -28

C) - (1/6)

D) (1/2)

8) y = √(2x - 1) between x = 1 and x = 5

A) -28

B) (1/2)

C) -2

D) - (1/6)

9) y = (3/x + 2) between x = 1 and x = 4

A) -2

B) (1/2)

C) -28

D) - (1/6)

10) y = 5x + 7 between x = -1 and x = 0

A) 5

B) (1/2)

C) - (1/6)

D) -28

Suppose the position of an object moving in a straight line is given by the specified function. Find the instantaneous velocity at time t.

11) s(t) = t2 + 6t + 4, t = 4

A) 32

B) 14

C) 12

D) 44

12) s(t) = t2 + 4t + 5, t = 1

A) 11

B) 6

C) 5

D) 10

13) s(t) = 5t2 - 7t - 3, t = 3

A) 21

B) 20

C) 8

D) 23

14) s(t) = t3 + 4t + 3, t = 2

A) 10

B) 8

C) 19

D) 16

15) s(t) = t3 + 4t + 3, t = 1

A) 10

B) 8

C) 7

D) 6

Find the instantaneous rate of change for the function at the given value.

16) F(x) = x2 + 7x at x = -8

A) -16

B) -1

C) 8

D) -9

17) f(x) = 5x + 9 at x = 2

A) 9

B) 10

C) 5

D) 0

18) s(t) = t2 + 5t at t = 4

A) 9

B) 21

C) 3

D) 13

19) g(t) = 5t2 + t at t = -4

A) -39

B) -41

C) -14

D) 6

20) F(x) = 2x2 + x - 3 at x = 4

A) 17

B) 15

C) 19

D) 5

21) g(x) = x2 + 11x - 15 at x = 1

A) 11

B) 13

C) -9

D) 26

22) s(t) = 3t2 + 5t - 7 at t = -2

A) -1

B) -17

C) -7

D) 1

23) g(t) = 3t2 + 6 at t = 4

A) 8

B) 12

C) 24

D) -24

## Solution 5 (1 Ratings )

Solved
Calculus 3 Months Ago 29 Views